A Controlled Study of Behavioral Inhibition in Children of Parents With Panic Disorder and Depression - Rosenbaum, Jerrold F.; Biederman, Joseph; Hirshfeld-Becker, Dina R.; Kagan, Jerome; Snidman, Nancy; Friedman, Deborah; Nineberg, Allan; Gallery, Daniel J.; Faraone, Stephen V. (The American journal of psychiatry, 2000)
OBJECTIVE: "Behavioral inhibition to the unfamiliar" has been proposed as a precursor to anxiety disorders. Children with behavioral inhibition are cautious, quiet, introverted, and shy in unfamiliar situations. Several lines of evidence suggest that behavioral inhibition is an index of anxiety proneness. The authors sought to replicate prior findings and examine the specificity of the association between behavioral inhibition and anxiety. METHOD: Laboratory-based behavioral observations were used to assess behavioral inhibition in 129 young children of parents with panic disorder and major depression, 22 children of parents with panic disorder without major depression, 49 children of parents with major depression without panic disorder, and 84 children of parents without anxiety disorders or major depression (comparison group). A standard definition of behavioral inhibition based on previous research ("dichotomous behavioral inhibition") was compared with two other definitions. RESULTS: Dichotomous behavioral inhibition was most frequent among the children of parents with panic disorder plus major depression (29% versus 12% in comparison subjects). For all definitions, the univariate effects of parental major depression were significant (conferring a twofold risk for behavioral inhibition), and for most definitions the effects of parental panic disorder conferred a twofold risk as well. CONCLUSIONS: These results suggest that the comorbidity of panic disorder and major depression accounts for much of the observed familial link between parental panic disorder and childhood behavioral inhibition. Further work is needed to elucidate the role of parental major depression in conferring risk for behavioral inhibition in children.